Reintroducing vacuum extraction in primary health care facilities: a case study from Tanzania - Dominico, Sunday (BMC Pregnancy Childbirth, 2018)
BACKGROUND: In rural Tanzania access to emergency obstetric and newborn care is threatened by poor roads and understaffed facilities among other challenges. Districts in Kigoma, Pwani and Morogoro regions were targeted by a local non-governmental organization to assist local government to build capacity and improve access to clinical management of severe obstetric and newborn complications. The program upgraded ten primary health care centres to provide comprehensive emergency obstetric and newborn care. This paper describes the process of reintroducing vacuum extraction into ten health centres and five hospitals, highlighting patterns in uptake, mode of delivery and lessons learned. METHODS: This observational study uses facility-based trend data collected between 2011 and 2016.Descriptive outcomes include institutional caesarean delivery rates, vacuum extraction rates, and the ratio of caesareans to vacuum-assisted deliveries. RESULTS: Institutional caesarean delivery rates remained stable at about 10–11% and the vacuum extraction rate rose from virtually no procedures in 2011 to about 2% in 2016. The increase was more visible in upgraded health centres than in hospitals. In 2016 vacuum extraction rates in newly upgraded health centres ranged from 0.5 to 7.8%. Between 2011 and 2016, the ratio of caesareans to vacuum extractions in hospitals changed from 304 caesareans to 1 vacuum extraction to 10:1, while in health centres the ratio changed from 22: 1 to 3: 1. CONCLUSIONS: Reintroduction of vacuum extraction into clinical practice in primary health care facilities with task-shifting is feasible. Reintroduction of this procedure was more successful when part of an integrated upgrading of health centres to provide comprehensive emergency obstetric care than when reintroduced into busy hospital environments. Turnover of trained staff in hospitals contributed to the uneven uptake of vacuum extraction. Lessons learned are applicable to further national scale up and to other countries.